Current Status and Challenges of Colorimetric Intelligent Packaging for Fruit and Vegetables: A Review - Fikrte Woldeyes Hailu; Solomon Workneh Fanta; Alemayehu Ambaw Tsige; Mulugeta Admasu Delele (Journal of Food Quality)
This review examines colorimetric indicator packaging approaches for fresh fruit and vegetable (F&V) products, focusing on freshness monitoring, quality considerations, and potential future issues. Currently, consumers increasingly need to know F&V provenance and more information on quality and safety attributes. Methods for determining the freshness of F&V were created to reduce consumer use of expired F&V. Due to their short shelf lives, F&Vs have experienced numerous physiologic, chemical, and biological changes throughout time. These techniques altered their perception of quality, safety, and freshness. Today, F&V can be tracked along with their qualities and storage life through the supply chain using colorimetric freshness indicators. Those indicators detect pH, gas, temperature, humidity, and microbial activity from F&V metabolites during storage. Of them, pH indicators displayed more active responses due to the F&V being past its expiration date. However, fresh F&V is not yet fully commercially usable for freshness monitoring systems. This is because the response of indicators for F&V was inferior when compared to protein-based foods such as fish and meat. The basic problem is that the released metabolites of F&V during storage, such as carbon dioxide, cannot easily make the environment a stronger acid for indicator detection than ammonia metabolites from protein foods. On the other hand, most indicators are developed from synthetic dyes and polymers, which could be a reason for health effects, while natural dyes and biopolymers do not effectively detect the target metabolites and withstand moisture. In the future, an additional study must be done on various freshness monitoring systems and their widespread use with fresh F&V.